KOMUNIKASI INTERPERSONAL FOTOGRAFER DALAM MEMPERTAHANKAN PELANGGAN - Musthova, Ivan; Riyanto, Buddy; Muadz, Muadz (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
This research aims to find out the problem solving related to the problems experienced by Wibi Febrian photographer in conducting an interpersonal communication activity in maintaining customer interest. This research is descriptive with qualitative analysis. Data collection techniques are done by interviewing informants from both Wibi Febrian and his service users. The results showed that interpersonal communication used by Wibi Febrian in maintaining its customers by applying 2 types of communication, namelyverbal and non-verbal communication between Wibi Febrian to its customers. Thereverse assessment was felt from the service users, because Wibi Febrian did not apply the 5 positive attitudes, namely in the form of not doing respect, empathy, audible, clarity and humble towards his customers. Keywords : Interpersonal Communication, Wibi Febrian and Customers